Gender Gap in Labor Supply, Leisure, Consumption, and Home Production and National Policy in Japan - Piao, Xiangdan; Nasuda, Akiko (Asian Journal of Empirical Research, 2021)
This study investigates single individuals’ different choices over time in terms of use (labor supply, home production time input, leisure) and consumption (market consumption goods, home production goods) and provides evidence to explain the differences. To this effect, we use the structural model of the Almost Ideal Demand System with a Cobb-Douglas home production function. The results are summarized as follows. Regarding labor supply, both women and men have the same working willingness in the labor market when women are paid as much as men. Overall, although the regional gender income gap appears different between major metropolitan areas and non-major metropolitan areas, our results indicate that the income gap would disappear by diminishing the wage gap. However, for home production, the gender gap persists when women apply the same conditions as men, although the gap is small. Policy implied that reducing the gender wage gap is an important tool to encourage single women to work as men in the workplace regardless of the area.